Biopiracy of natural products and good bioprospecting practice - Efferth, Thomas; Banerjee, Mita; Paul, Norbert W.; Abdelfatah, Sara; Arend, Joachim; Elhassan, Gihan; Hamdoun, Sami; Hamm, Rebecca; Hong, Chunlan; Kadioglu, Onat; Nass, Janine; Ochwangi, Dominic; et al. (Elsevier B.V., 2016)
Background: Biopiracy mainly focuses on the use of biological resources and/or knowledge of indigenous tribes or communities without allowing them to share the revenues generated out of economic exploitation or other non-monetary incentives associated with the resource/knowledge. Methods: Based on collaborations of scientists from five continents, we have created a communication platform to discuss not only scientific topics, but also more general issues with social relevance. This platform was termed 'PhytCancer -Phytotherapy to Fight Cancer' (www.phyt-cancer.uni-mainz.de). As a starting point, we have chosen the topic biopiracy, since we feel this is of pragmatic significance for scientists working with medicinal plants. Results: It was argued that the patenting of herbs or natural products by pharmaceutical corporations disregarded the ownership of the knowledge possessed by the indigenous communities on how these substances worked. Despite numerous court decisions in U.S.A. and Europe, several international treaties, (e.g. from United Nations, World Health Organization, World Trade Organization, the African Unity and others), sharing of a rational set of benefits amongst producers (mainly pharmaceutical companies) and indigenous communities is yet a distant reality. In this paper, we present an overview of the legal frameworks, discuss some exemplary cases of biopiracy and bioprospecting as excellent forms of utilization of natural resources. Conclusions: We suggest certain perspectives, by which we as scientists, may contribute towards prevention of biopiracy and also to foster the fair utilization of natural resources. We discuss ways, in which the interests of indigenous people especially from developing countries can be secured. (C) 2015 Elsevier GmbH. All rights reserved.
Keywords: Bioethics; Bioprospecting; Commercialization; Indigenous knowledge; Intellectual property; Patent